Table of contents

Variational formulation of the rod element

In what follows we shall derive the FEM for the rod element using the weak form of the elasticity equation and tangential calculus.

Unlike the direct approach, we will introduce a framework for developing FEM on continuum elements more generally. The resulting linear system will be exactly the same as for the direct approach. However, this approach is more general and applicable to other element types.

A truss system is made of rod elements which only carry loads axially, they still obey the principal of minimum potential energy and the weak form of the elasticity equation.

Consider the following truss system of rods in 2D. We have 3 nodes and 3 elements. The problem states:

Find the displacements of the nodes, uu, such that

Ωσ(u):ε(v)dΩ=ΩfvdΩ+Ωtvdsv that are 0 on ΩD\boxed{ \int_{\Omega } \bm \sigma (\bm u) : \bm \varepsilon \left( \bm v\right) d\Omega =\int_{\Omega } \bm f\cdot \bm vd\Omega +\int_{\partial \Omega } \bm{t} \cdot \bm v ds \quad \forall v \text{ that are } 0 \text{ on } \partial \Omega_D}

holds under the boundary conditions

[u1x,u1y,u3x]=0 and f2y=P.\left\lbrack u_1^x ,u_1^y ,u_3^x \right\rbrack =0 \text{ and } f_2^y =-P.

Consider a rod element in 2D

A rod element is defined by having two nodes, connected by a straight line. The nodal displacements are denoted by u1\bm u_1 and u2\bm u_2 and correspond to the nodal positions x1\bm x_1 and x2\bm x_2. For simplicity we shall define the following in a 2D setting. The element can be arbitrarily oriented in space, we define the angle between the x-axis and the rod as θ\theta. The tangential vector is given by t=x2x1x2x1\bm t=\frac{ \bm x_2 -\bm x_1 }{|\bm x_2 -\bm x_1 |} and the normal vector is defined as n=ez×t\bm n={\bm e }_z \times \bm t. We note that the tangential vector and the normal vector can be expressed using θ\theta.

t=[cosθ,sinθ]\bm t=\left\lbrack \cos \theta ,\sin \theta \right\rbrack n=[sinθ,cosθ]\bm n=\left\lbrack -\sin \theta ,\cos \theta \right\rbrack

We know from the definition of the element that it only carries axial loads, i.e., in-line loads. Thus the in-line strain has to be

ε~=[uxxt000] \tilde{\bm \varepsilon} =\left\lbrack \begin{array}{cc} \dfrac{\partial u_x }{\partial x_t } & 0\\ 0 & 0 \end{array}\right\rbrack

where \sim denotes the strain tensor in local coordinates. The tt (tangential) subindex in xt\frac{\partial }{\partial x_t } denotes that the derivatives are in-line with the element.

In essence, we need to compute the strain tensor such that it has no out of line components, i.e., we need to define an in-line strain tensor, εtP\bm \varepsilon_t^P such that

nεtPn=0\bm n\cdot \bm \varepsilon_t^P \cdot \bm n=0

using this tensor, our weak form takes the form

EΩεtP(u):εtP(v)dΩ=Ωfv  d  Ω+Ωtvdsv=0  on  Ω E\int_{\Omega } \bm \varepsilon_t^P \left(\bm u\right) : \bm \varepsilon_t^P \left(\bm v\right)d\Omega =\int_{\Omega } \bm f\cdot \bm v\;d\;\Omega +\int_{\partial \Omega } \bm t\cdot \bm v ds \quad \forall v=0 \; \textrm{on}\;\partial \Omega

Computing in-line derivatives

We need to compute uxxt\frac{\partial u_x }{\partial x_t } numerically.

The parametric map

We begin by constructing a parametric map for the rod element. The tt direction of the rod will be mapped to the ξ\xi -direction and n  n\;to η\eta such that any point on the physical rod can be expressed by ξ\xi and η\eta as such

x(ξ,η)=φ1(ξ)x1+φ2(ξ)x2+ηn=x1+ξ(x2x1)+ηn \bm x (\xi ,\eta ) = \varphi_1 (\xi) \bm x_1 +\varphi_2 (\xi) \bm x_2 + \eta \bm n = \bm x_1 + \xi \left( \bm x_2 - \bm x_1 \right) + \eta \bm n

where φ=[1ξ,ξ]\varphi =\left\lbrack 1-\xi ,\xi \right\rbrack are the basis functions for the rod element and we let η[r,r]\eta \in \left\lbrack -r,r\right\rbrack parametrize the thickness of the rod within a radius rr around the centerline.

Now, let the gradient of the displacements

u=[uxxuyxuxyuyy] \def\arraystretch{2.5} \nabla \bm u = \left\lbrack \begin{array}{cc} \dfrac{\partial u_x }{\partial x} & \dfrac{\partial u_y }{\partial x}\\ \dfrac{\partial u_x }{\partial y} & \dfrac{\partial u_y }{\partial y} \end{array}\right\rbrack

We can approximate the derivative using the basis functions, e.g.:

uxxiφixuix=φ1xu1x+φ2xu2x\dfrac{\partial u_x }{\partial x}\approx \sum_i \dfrac{\partial \varphi_i }{\partial x}u_i^x =\dfrac{\partial \varphi_1 }{\partial x}u_1^x +\dfrac{\partial \varphi_2 }{\partial x}u_2^x

which is exact for the rod element, since we assume pure linear deformation.

We can get the derivatives of the basis functions with respect to the spatial variables by the chain rule:

[φξφη]=[xξyξxηyη]J[φxφy] \def\arraystretch{2.5} \left\lbrack \begin{array}{c} \dfrac{\partial \varphi }{\partial \xi }\\ \dfrac{\partial \varphi }{\partial \eta } \end{array}\right\rbrack =\underset{\bm J }{\underbrace{\left\lbrack \begin{array}{cc} \dfrac{\partial x}{\partial \xi } & \dfrac{\partial y}{\partial \xi }\\ \dfrac{\partial x}{\partial \eta } & \dfrac{\partial y}{\partial \eta } \end{array}\right\rbrack } } \left\lbrack \begin{array}{c} \dfrac{\partial \varphi }{\partial x}\\ \dfrac{\partial \varphi }{\partial y} \end{array}\right\rbrack

where we identify J\bm J as the Jacobian matrix.

J:=[xξyξxηyη]=rod element[x2x1y2y1nxny]=[x2x1y2y1sinθcosθ] \def\arraystretch{2.5} \bm J:=\left\lbrack \begin{array}{cc} \dfrac{\partial x}{\partial \xi } & \dfrac{\partial y}{\partial \xi }\\ \dfrac{\partial x}{\partial \eta } & \dfrac{\partial y}{\partial \eta } \end{array}\right\rbrack \overset{\text{rod element} }{=} \left\lbrack \begin{array}{cc} x_2 -x_1 & y_2 -y_1 \\ n_x & n_y \end{array}\right\rbrack =\left\lbrack \begin{array}{cc} x_2 -x_1 & y_2 -y_1 \\ -\sin \theta & \cos \theta \end{array}\right\rbrack

The determinant of the Jacobian is a measure of how scaled the size of the physical element is compared to the reference element, i.e., it should be the length, LL for the rod element. Let us check this:

detJ=Δxcosθ+Δysinθ\det \bm J =\Delta x\cos \theta +\Delta y\sin \theta

with the geometric relation Δx=L  cosθ\Delta x=L\;\cos \theta and Δy=L  sinθ\Delta y=L\;\sin \theta we have

detJ=Lcos2θ+Lsin2θ=L\det \bm J =L\cos^2 \theta +L\sin^2 \theta =L

Now, the relation (11) can be inverted to get the sought derivatives.

[φxφy]=J1[φξφη] \def\arraystretch{2.5} \left\lbrack \begin{array}{c} \dfrac{\partial \varphi }{\partial x}\\ \dfrac{\partial \varphi }{\partial y} \end{array}\right\rbrack =\bm J^{-1} \left\lbrack \begin{array}{c} \dfrac{\partial \varphi }{\partial \xi }\\ \dfrac{\partial \varphi }{\partial \eta } \end{array}\right\rbrack

Let

B^:=[φξφη]=rod  element[1100] \def\arraystretch{2.5} \hat{\mathbf{B} } :=\left\lbrack \begin{array}{c} \dfrac{\partial \varphi }{\partial \xi }\\ \dfrac{\partial \varphi }{\partial \eta } \end{array}\right\rbrack \overset{\textrm{rod}\;\textrm{element} }{=} \left\lbrack \begin{array}{cc} -1 & 1\\ 0 & 0 \end{array}\right\rbrack

then

[φxφy]=:B=J1B^=rod  element1L[cosθcosθsinθsinθ] \def\arraystretch{2.5} \left\lbrack \begin{array}{c} \dfrac{\partial \varphi }{\partial x}\\ \dfrac{\partial \varphi }{\partial y} \end{array}\right\rbrack =:\mathbf{B} = \bm J^{-1} \hat{\mathbf{B} } \overset{\textrm{rod}\;\textrm{element} }{=} \dfrac{1}{L}\left\lbrack \begin{array}{cc} -\cos \theta & \cos \theta \\ -\sin \theta & \sin \theta \end{array}\right\rbrack

The tangential projection using tangential differential calculus

We derive this model using the approach by [1] and [2]. Let

U=[u1xu1yu2xu2y]\mathbf{U}=\left\lbrack \begin{array}{cc} u_1^x & u_1^y \\ u_2^x & u_2^y \end{array}\right\rbrack

and we can compute the approximate gradient of U\mathbf U by

U=BU=rod  element[φ1xφ2xφ1yφ2y][u1xu1yu2xu2y]=[uxxuyxuxyuyy] \def\arraystretch{2.5} \nabla \mathbf U = \mathbf{B} \mathbf U \overset{\textrm{rod}\;\textrm{element} }{=} \left\lbrack \begin{array}{cc} \dfrac{\partial \varphi_1 }{\partial x} & \dfrac{\partial \varphi_2 }{\partial x}\\ \dfrac{\partial \varphi_1 }{\partial y} & \dfrac{\partial \varphi_2 }{\partial y} \end{array}\right\rbrack \left\lbrack \begin{array}{cc} u_1^x & u_1^y \\ u_2^x & u_2^y \end{array}\right\rbrack =\left\lbrack \begin{array}{cc} \dfrac{\partial u_x }{\partial x} & \dfrac{\partial u_y }{\partial x}\\ \dfrac{\partial u_x }{\partial y} & \dfrac{\partial u_y }{\partial y} \end{array}\right\rbrack

and the typical engineering strain tensor is given by

ε=12(uT+u)\bm \varepsilon =\dfrac{1}{2}\left(\nabla \bm u^T +\nabla \bm u\right)

The problem with this tensor is that it is not in-line, i.e., nεn0\bm n\cdot \bm \varepsilon \cdot \bm n\not= 0

We can instead use

εt=12(tuT+tu)\bm \varepsilon_t =\dfrac{1}{2}\left(\nabla_t \bm u^T +\nabla_t \bm u\right)

where

tu:=Ptu\nabla_t \bm u := \bm P_t \nabla \bm u

and Pt\bm P_t is known as the tangential projection operator that maps onto the tangent line of the rod. Recall

where v\bm v is some out-of-line vector, we can get the in-line vector vt\bm v_t by

vt=vvn \bm v_t =\bm v - \bm v_n

with

vn=n(nv)\bm v_n = \bm n\left(\bm n\cdot \bm v\right)

Recalling the tensor (outer) product (ab)ij=aibj{\left(\bm a\otimes \mathbf{b}\right)}_{\textrm{ij} } =a_i b_j we can use the tensor product rule (ab)c=a(bc)\left(\bm a\otimes \mathbf{b}\right)\bm c=\bm a\left(\mathbf{b}\cdot \bm c\right) and get vt=v(nn)v\bm v_t =\bm v-\left(\bm n\otimes \bm n\right)\bm v which can be rewritten into

vt=(Inn)v=:Ptv\bm v_t =\left(\bm I-\bm n\otimes \bm n\right)\bm v=:{\bm P }_t \bm v

Note that the projection operator also can be written using the tangential vector

Pt=tt\bm P_t =\bm t\otimes \bm t

which has some benefits, since the normal can be hard to define in 3D, especially for the rod.

Using t=[cosθsinθ]=[cs]\bm t=\left\lbrack \begin{array}{cc} \cos \theta & \sin \theta \end{array}\right\rbrack =\left\lbrack \begin{array}{cc} c & s \end{array}\right\rbrack we get the projection operator

Pt=[cs][cs]=[c2cscss2]=(Inn)=[1001][sc][sc]=[1s2cscs1c2]\bm P_t =\left\lbrack \begin{array}{c} c\\ s \end{array}\right\rbrack \left\lbrack \begin{array}{cc} c & s \end{array}\right\rbrack =\left\lbrack \begin{array}{cc} c^2 & \textrm{cs}\\ \textrm{cs} & s^2 \end{array}\right\rbrack =\left(\bm I-\bm n\otimes \bm n\right)=\left\lbrack \begin{array}{cc} 1 & 0\\ 0 & 1 \end{array}\right\rbrack -\left\lbrack \begin{array}{c} -s\\ c \end{array}\right\rbrack \left\lbrack \begin{array}{cc} -s & c \end{array}\right\rbrack =\left\lbrack \begin{array}{cc} 1-s^2 & \textrm{cs}\\ \textrm{cs} & 1-c^2 \end{array}\right\rbrack

The problem of using εt\bm \varepsilon_t as a measure of strain on the rod is that it is not an in-line tensor, i.e., εtn0\bm \varepsilon_t \cdot \bm n \not = \bm 0. Using this tensor we get shear strains associated with the out-of-line direction. To obtain a pure in-line strain tensor we need to apply the projection twice to define

εtP:=PtεPt\bm \varepsilon_t^P := \bm P_t \bm \varepsilon \bm P_t

which does not contain any out-of-line strain components, i.e., both the rows and columns of εtP\bm \varepsilon_t^P are tangent vectors such that εtPn=nεtP=0\bm \varepsilon_t^P \cdot \bm n = \bm n \cdot \bm \varepsilon_t^P = \bm 0 .

A detailed look at the strain tensor using θ=0\theta =0 such that n=[0,1]\bm n=\left\lbrack 0,1\right\rbrack and t=[1,0]\bm t=\left\lbrack 1,0\right\rbrack we get

Pt=[1000],tu=Ptu=[1000][uxxuyxuxyuyy]=[uxxuyx00], \def\arraystretch{2.5} \bm P_t =\left\lbrack \begin{array}{cc} 1 & 0\\ 0 & 0 \end{array}\right\rbrack ,\nabla_t \bm u = \bm P_t \nabla u=\left\lbrack \begin{array}{cc} 1 & 0\\ 0 & 0 \end{array}\right\rbrack \left\lbrack \begin{array}{cc} \dfrac{\partial u_x }{\partial x} & \dfrac{\partial u_y }{\partial x}\\ \dfrac{\partial u_x }{\partial y} & \dfrac{\partial u_y }{\partial y} \end{array}\right\rbrack =\left\lbrack \begin{array}{cc} \dfrac{\partial u_x }{\partial x} & \dfrac{\partial u_y }{\partial x}\\ 0 & 0 \end{array}\right\rbrack , εt=12([uxx0uyx0]+[uxxuyx00])[uxx12uyx12uyx0] \def\arraystretch{2.5} \bm \varepsilon_t =\dfrac{1}{2}\left(\left\lbrack \begin{array}{cc} \dfrac{\partial u_x }{\partial x} & 0\\ \dfrac{\partial u_y }{\partial x} & 0 \end{array}\right\rbrack +\left\lbrack \begin{array}{cc} \dfrac{\partial u_x }{\partial x} & \dfrac{\partial u_y }{\partial x}\\ 0 & 0 \end{array}\right\rbrack \right)\left\lbrack \begin{array}{cc} \dfrac{\partial u_x }{\partial x} & \dfrac{1}{2}\dfrac{\partial u_y }{\partial x}\\ \dfrac{1}{2}\dfrac{\partial u_y }{\partial x} & 0 \end{array}\right\rbrack

and

εtP=[uxx000] \def\arraystretch{2.5} \bm \varepsilon_t^P =\left\lbrack \begin{array}{cc} \dfrac{\partial u_x }{\partial x} & 0\\ 0 & 0 \end{array}\right\rbrack
⚠ Note

In the case of the rod we have the property

PtB=B\bm P_t \mathbf{B} = \mathbf{B}

Meaning that the derivatives of the basis functions for the rod element are in-line.

Recall

B=1L[ccss]\mathbf{B}=\dfrac{1}{L}\left\lbrack \begin{array}{cc} -c & c\\ -s & s \end{array}\right\rbrack

then

PtB=[c2c  sc  ss2]1L[ccss]=1L[c(c2+s2)c(c2+s2)s(c2+s2)s(c2+s2)] \def\arraystretch{1.5} \bm P_t \mathbf B = \left\lbrack \begin{array}{cc} c^2 & c\;s\\ c\;s & s^2 \end{array}\right\rbrack \dfrac{1}{L}\left\lbrack \begin{array}{cc} -c & c\\ -s & s \end{array}\right\rbrack =\dfrac{1}{L}\left\lbrack \begin{array}{cc} -c\left(c^2 +s^2 \right) & c\left(c^2 +s^2 \right)\\ -s\left(c^2 +s^2 \right) & s\left(c^2 +s^2 \right) \end{array}\right\rbrack

which can also be checked with e.g.,

Ptt=[c2c  sc  ss2][cs]=[c(c2+s2)s(c2+s2)]=t \def\arraystretch{1.5} \bm P_t \bm t=\left\lbrack \begin{array}{cc} c^2 & c\;s\\ c\;s & s^2 \end{array}\right\rbrack \left\lbrack \begin{array}{c} c\\ s \end{array}\right\rbrack =\left\lbrack \begin{array}{c} c\left(c^2 +s^2 \right)\\ s\left(c^2 +s^2 \right) \end{array}\right\rbrack = \bm t Ptn=[c2c  sc  ss2][sc]=[c2sc2scs2cs2]=[00] \def\arraystretch{1.5} \bm P_t \bm n = \left\lbrack \begin{array}{cc} c^2 & c\;s\\ c\;s & s^2 \end{array}\right\rbrack \left\lbrack \begin{array}{c} -s\\ c \end{array}\right\rbrack =\left\lbrack \begin{array}{c} c^2 s-c^2 s\\ {\textrm{cs} }^2 -{\textrm{cs} }^2 \end{array}\right\rbrack =\left\lbrack \begin{array}{c} 0\\ 0 \end{array}\right\rbrack

Now that we have an in-line strain tensor we need to implement it into the weak form. We need to compute εtP(u):εtP(v)\bm \varepsilon_t^P \left(\bm u\right): \bm \varepsilon_t^P \left(\bm v\right) numerically, which can be made easier by working with εt\bm \varepsilon_t instead. Using the vector analogy for removing the normal components of the vector, but applied on tensors following the approach by Hansbo and Larson [2], we have for our strain tensor:

εtP=εt(εtn)n+n(εtn) \bm \varepsilon_t^P = \bm \varepsilon_t -\left(\bm \varepsilon_t \cdot \bm n\right)\otimes \bm n+\bm n\otimes \left( \bm \varepsilon_t \cdot \bm n\right)

and the double-dot product

εtP(u):εtP(v)=εt(u):εt(v)2(εt(u)n)(εt(v)n) \bm \varepsilon_t^P \left(\bm u \right) : \bm \varepsilon_t^P \left(\bm v \right)= \bm \varepsilon_t \left(\bm u \right) : \bm \varepsilon_t \left( \bm v \right) - 2\left(\bm \varepsilon_t \left(\bm u \right)\cdot \bm n \right) \cdot \left(\bm \varepsilon_t \left(\bm v\right)\cdot \bm n\right)

Applying Hooke's law for a 1D element, i.e., the in-line stress tensor,

σtP=EεtP \bm \sigma_t^P = E \bm \varepsilon_t^P

Thus we arrive at the rod equation, find u\bm u such that

EΩεt(u):εt(v)dΩEΩ2(εt(u)n)(εt(v)n)dΩ=Ωfv  d  Ω+Ωtv  dsv=0  on  ΩE\int_{\Omega } \bm \varepsilon_t \left(\bm u\right): \bm \varepsilon_t \left(\bm v\right)d\Omega -E\int_{\Omega } 2\left(\bm \varepsilon_t \left(\bm u\right)\cdot \bm n\right)\cdot \left(\bm \varepsilon_t \left(\bm v\right)\cdot \bm n\right)d\Omega =\int_{\Omega } \bm f\cdot \bm v\;d\;\Omega +\int_{\partial \Omega } \bm t\cdot \bm v\;\textrm{ds} \quad \forall \bm v=0\;\textrm{on}\;\partial \Omega

The Voigt/ Mandel form

The approximation of the solution vector for the rod element KK:

uK(x)UK(x)=[φ1(x)0φ2(x)00φ1(x)0φ2(x)]Φ[u1xu1yu2xu2y]u=[φ1(x)u1x+φ2(x)u2xφ1(x)u1y+φ2(x)u2y]=[UxUy]=U(x) \def\arraystretch{1.5} \begin{array}{l} \bm u_K \left(\bm x \right)\approx {\mathbf U }_K \left(\bm x\right)=\underset{\Phi }{\underbrace{\left\lbrack \begin{array}{cccc} \varphi_1 \left(\bm x\right) & 0 & \varphi_2 \left(\bm x\right) & 0\\ 0 & \varphi_1 \left(\bm x\right) & 0 & \varphi_2 \left(\bm x\right) \end{array}\right\rbrack } } \underset{\mathbf{u} }{\underbrace{\left\lbrack \begin{array}{c} u_1^x \\ u_1^y \\ u_2^x \\ u_2^y \end{array}\right\rbrack } } \\ =\left\lbrack \begin{array}{c} \varphi_1 \left(\bm x\right)u_1^x +\varphi_2 \left(\bm x\right)u_2^x \\ \varphi_1 \left(\bm x\right)u_1^y +\varphi_2 \left(\bm x\right)u_2^y \end{array}\right\rbrack =\left\lbrack \begin{array}{c} U_x \\ U_y \end{array}\right\rbrack =\mathbf U\left(\bm x\right) \end{array}

The mandel notation for the strain tensor is

εM(u)=[ε11ε222ε12][x00y12y12x][UxUy]=[UxxUyy12Uxy+12Uyx] \def\arraystretch{2.5} \bm \varepsilon_M \left(\bm u\right)=\left\lbrack \begin{array}{c} \varepsilon_{11} \\ \varepsilon_{22} \\ \sqrt{2}\varepsilon_{12} \end{array}\right\rbrack \approx \left\lbrack \begin{array}{cc} \dfrac{\partial }{\partial x} & 0\\ 0 & \dfrac{\partial }{\partial y}\\ \dfrac{1}{\sqrt{2} }\dfrac{\partial }{\partial y} & \dfrac{1}{\sqrt{2} }\dfrac{\partial }{\partial x} \end{array}\right\rbrack \left\lbrack \begin{array}{c} U_x \\ U_y \end{array}\right\rbrack =\left\lbrack \begin{array}{c} \dfrac{\partial U_x }{\partial x}\\ \dfrac{\partial U_y }{\partial y}\\ \dfrac{1}{\sqrt{2} }\dfrac{\partial U_x }{\partial y}+\dfrac{1}{\sqrt{2} }\dfrac{\partial U_y }{\partial x} \end{array}\right\rbrack

The double contraction on Mandel form becomes

ε(u):ε(v)=εM(u)εM(v) \bm \varepsilon \left(\bm u\right) : \bm \varepsilon \left(\bm v\right) = \bm \varepsilon_M \left(\bm u\right)\cdot \bm \varepsilon_M \left(\bm v\right)

thus we have

εt(u):εt(v)=εMt(u)εMt(v)=BεTBεu \bm \varepsilon_t \left(\bm u\right): \bm \varepsilon_t \left(\bm v\right) = \bm \varepsilon_{\textrm{Mt} } \left(\bm u\right)\cdot \bm \varepsilon_{\textrm{Mt} } \left(\bm v\right)={\mathbf{B} }_{\bm \varepsilon }^T {\mathbf{B} }_{\varepsilon } \mathbf{u}

where

Bε:=[φ1x0φ2x00φ1y0φ2y12φ1y12φ1x12φ2y12φ2x] \def\arraystretch{2.5} \mathbf{B}_{\varepsilon } :=\left\lbrack \begin{array}{cccc} \dfrac{\partial \varphi_1 }{\partial x} & 0 & \dfrac{\partial \varphi_2 }{\partial x} & 0\\ 0 & \dfrac{\partial \varphi_1 }{\partial y} & 0 & \dfrac{\partial \varphi_2 }{\partial y}\\ \dfrac{1}{\sqrt{2} }\dfrac{\partial \varphi_1 }{\partial y} & \dfrac{1}{\sqrt{2} }\dfrac{\partial \varphi_1 }{\partial x} & \dfrac{1}{\sqrt{2} }\dfrac{\partial \varphi_2 }{\partial y} & \dfrac{1}{\sqrt{2} }\dfrac{\partial \varphi_2 }{\partial x} \end{array}\right\rbrack

and for the normal term, we get

(εt(u)n)(εt(v)n)=BnTBnu \left(\bm \varepsilon_t \left(\bm u\right)\cdot \bm n\right)\cdot \left(\bm \varepsilon_t \left(\bm v\right)\cdot \bm n\right)={\mathbf{B} }_n^T {\mathbf{B} }_n \mathbf{u}

where

Bn=[nxΦ1x+12ny(Φ1y+Φ2x)12nx(Φ1y+Φ2x)+nyΦ2y] {\mathbf{B} }_n =\left\lbrack \begin{array}{c} n_x \Phi_{1x} +\dfrac{1}{2}n_y \left(\Phi_{1y} +\Phi_{2x} \right)\\ \dfrac{1}{2}n_x \left(\Phi_{1y} +\Phi_{2x} \right)+n_y \Phi_{2y} \end{array}\right\rbrack

with

Φ1x=[φ1x0φ2x0]Φ2x=[0φ1x0φ2x]Φ1y=[φ1y0φ2y0]Φ2y=[0φ1y0φ2y]\begin{array}{l} \Phi_{1x} =\left\lbrack \begin{array}{cccc} \dfrac{\partial \varphi_1 }{\partial x} & 0 & \dfrac{\partial \varphi_2 }{\partial x} & 0 \end{array}\right\rbrack \\ \Phi_{2x} =\left\lbrack \begin{array}{cccc} 0 & \dfrac{\partial \varphi_1 }{\partial x} & 0 & \dfrac{\partial \varphi_2 }{\partial x} \end{array}\right\rbrack \\ \Phi_{1y} =\left\lbrack \begin{array}{cccc} \dfrac{\partial \varphi_1 }{\partial y} & 0 & \dfrac{\partial \varphi_2 }{\partial y} & 0 \end{array}\right\rbrack \\ \Phi_{2y} =\left\lbrack \begin{array}{cccc} 0 & \dfrac{\partial \varphi_1 }{\partial y} & 0 & \dfrac{\partial \varphi_2 }{\partial y} \end{array}\right\rbrack \end{array} ΩE(BεTBε2BnTBn)udΩ=ΩE(BεTBε2BnTBn)dΩ    u \int_{\Omega } E\left({\mathbf{B} }_{\varepsilon }^T {\mathbf{B} }_{\varepsilon } -2{\mathbf{B} }_n^T {\mathbf{B} }_n \right)\mathbf{u} d\Omega =\int_{\Omega } E\left({\mathbf{B} }_{\varepsilon }^T {\mathbf{B} }_{\varepsilon } -2{\mathbf{B} }_n^T {\mathbf{B} }_n \right) d\Omega \;\;\mathbf{u} Se=ΩE(BεTBε2BnTBε)dΩ=rr01E(BεTBε2BnTBε)detJdξdη=EAL(BεTBε2BnTBε) \bm S_{e}=\int_{\Omega}E\left(\mathbf{B}_{\varepsilon}^{T}\mathbf{B}_{\varepsilon}-2\mathbf{B}_{n}^{T}\mathbf{B}_{\varepsilon}\right)d\Omega=\int_{-r}^{r}\int_{0}^{1}E\left(\mathbf{B}_{\varepsilon}^{T}\mathbf{B}_{\varepsilon}-2\mathbf{B}_{n}^{T}\mathbf{B}_{\varepsilon}\right)\det\bm{J}d\xi d\eta=EAL\left(\mathbf{B}_{\varepsilon}^{T}\mathbf{B}_{\varepsilon}-2\mathbf{B}_{n}^{T}\mathbf{B}_{\varepsilon}\right)

As for the right-hand side, we can let f=0\bm f = \bm 0 i.e., no body load and Ωtvds\int_{\partial \Omega } \bm t \cdot \bm v ds is equivalent to a point load, since the boundary on a rod is just a node. So we treat point loads exactly the same way as in the Systematic Truss Analysis section.

Discussion

The theory herein serves to unify the 2D elasticity theory with the direct approach and incorporate the rod element into the same framework. The complexity arises when an element of lower dimension is used, as is the case with our rod element which essentially is R1\mathbb R^1 but embedded into R2\mathbb R^2 space. That mapping from 1D to 2D is traditionally done using rotational matrices and tricks, which can be omitted using tangential calculus.

References

[1]
M. Delfour and J.-P. Zolésio, “Differential equations for linear shells: Comparison between intrinsic and classical models.” pp. 41–124, 1997. doi: 10.1090/crmp/011/04.
[2]
P. Hansbo and M. G. Larson, “Finite element modeling of a linear membrane shell problem using tangential differential calculus,” vol. 270, pp. 1–14, 2014, doi: 10.1016/j.cma.2013.11.016.